DIVERSITAS FLORA DI BUKIT ABAH, KABUPATEN KLUNGKUNG UNTUK MENDUKUNG PENGEMBANGAN EKOWISATA - Rai, I.N.; Sukewijaya, I Made; Gunadi, I Gusti Alit (Bumi Lestari; Vol 9 No 1 (2009), 2009)
Goverment of Klungkung Regency, Bali province has a plan to develop an ecotourism area at Bukit Abah. The area is located within Besan Village, District of Dawan. In associated with this plan, a study has been conducted to identify the availability of diversity of flora in this site. The study was conducted by plant type stocktaking and analysis of vegetation methods. Results of plant type stocktaking shown that there were 126 plant species in the area, which were classified into 54 families. In addition, the analysis of vegetation indicated that there were a wide diversity of plants identified in Bukit Abah, with a diversity index (H) of >1.5. The high diversity of flora on the site had made a potential of attractive attention for developing of ecotourism in this area. It is suggested to accomplish an informative plantation labeling and vegetation conservation in associated with the development of the ecotourism plan
Keywords: vegetation; stocktaking; ecotourism; diversity index